FACTORS AFFECTING THE QUALITY MANAGEMENT SYSTEM AT THE ENTERPRISE - MAZUR, Dmytro; MAZUR, Oleksandr; MAZUR, Galina; KOVBII, Antonina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the current state of factors affecting the quality management system at the enterprise. The essence of the factors that affect the improvement of the quality control system at the enterprise is revealed. Types of factors are defined: external and internal. It is noted that the macro environment of the enterprise is based on the factors, but the enterprise may not control and these facts will affect the work of the enterprise. The factors of the microenvironment affecting the quality management system at the enterprise are shown Factors affecting the improvement of the quality control system at the enterprise and the functioning of the enterprise in the domestic market are identified. It was revealed that the company’s quality management system is aimed at ensuring the company’s competitiveness and expanding, while maintaining sales markets. It was found that the factors of the internal environment of the enterprise (technical and technological, organizational, economic and social) influence and improve the quality management system of the enterprise The factors and how the enterprise gets used to the changing conditions with their help are studied. It is shown how the influence of internal and external factors on the quality management system at the enterprise can negatively affect the company’s activities.